Issues Of Patriotic Education In Spiritual Heritage (Eurasian Journal of Learning and Academic Teaching, 2023)
Current article highlights the issues of patriotic education in the spiritual heritage of our people, particularly, the ways of developing patriotic education of military personnel on the example of the bravery of our ancestors.